1992
DOI: 10.1002/jrs.1250231202
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared spectra, conformational stability, barriers to internal rotation, vibrational assignment, and ab initio calculations for 3‐iodopropene

Abstract: The Raman spectra (3200-10 cm-') of gaseous, liquid and solid and infrared spectra (3200-40 cm-') of gaseous and solid 3-iodopropene, H,C=CHCH,I, were recorded. The fundamental asymmetric torsional transition of the most stable gauche conformer was observed in the Raman and far-infrared spectra of the gas at 95 cm-l. In the Raman spectrum of the liquid a second C-I stretch and two skeletal bending modes were identified for the less stable cis conformer. From a study of the Raman spectrum of the liquid at vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The structural parameters, conformational stability, and vibrational spectra of the 3-monosubstituted propenes, CH 2 CHCH 2 X, where X = F, , Cl, Br, , I, CN, CH 3 , SiH 3 , NH 2 , OH, , etc., have been of interest for several years. For the 3-halopropenes (allyl halides) only the fluoride has the syn conformer as the more stable rotamer, but many of the ab initio calculations at the MP2 level with full electron correlation utilizing relatively large basis sets with diffuse functions predict the gauche conformer as the more stable form.…”
Section: Introductionmentioning
confidence: 99%
“…The structural parameters, conformational stability, and vibrational spectra of the 3-monosubstituted propenes, CH 2 CHCH 2 X, where X = F, , Cl, Br, , I, CN, CH 3 , SiH 3 , NH 2 , OH, , etc., have been of interest for several years. For the 3-halopropenes (allyl halides) only the fluoride has the syn conformer as the more stable rotamer, but many of the ab initio calculations at the MP2 level with full electron correlation utilizing relatively large basis sets with diffuse functions predict the gauche conformer as the more stable form.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent investigation~ have included the determination of the potential functions governing internal rotation about the ~( s p~) -~( s p ' ) bonds of the parent 3-halopropenes and some substituted derivatives (24)(25)(26)(27)(28)(29)(30)(31)(32). Ally1 fluoride (24)(25)(26), chloride (27), bromide (28,31), and iodide (32) have been determined to exist as a mixture of syn and gauche conformers, and for the fluoride we have shown that the conformer that has the halogen atom syn to the double bond is the more stable rotamer (24)(25)(26). For 3-chloropropene, the value of the energy difference (27) was inferred to be less than 100 cm-' (286 cal/mol) and the spectral data merely indicated a very slight preference for the syn conformer for the gaseous state.…”
Section: Introductionmentioning
confidence: 99%
“…For 3-chloropropene, the value of the energy difference (27) was inferred to be less than 100 cm-' (286 cal/mol) and the spectral data merely indicated a very slight preference for the syn conformer for the gaseous state. For allyl bromide (28,31) and iodide (32) the gauche structure is thermodynamically preferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural parameters, conformational stability, and vibrational spectra of the 3-monosubstituted propenes, CH 2 = CHCH 2 X, where X ¼ F, 1,2 Cl, 3 Br, 4,5 I, 6 CN, 7 CH 3 , 8 SiH 3 , 9 NH 2 , [10][11][12][13] OH, 14,15 C= =CH, 16 etc. have been of interest for many years.…”
Section: Introductionmentioning
confidence: 99%